Preparation method and application of antibacterial nano composite fiber membrane
By constructing the Z-type heterojunction of ZIF-8/FeWOx nanocomposite and loading it onto the TPU fiber membrane, the problem of low internal electron efficiency of existing MOFs materials under visible light conditions is solved, and photocatalysis, photothermal, Magnetothermal synergistic antibacterial effect can kill 99.99% on a variety of drug-resistant bacteria.
Patent Information
- Application Number
- CN202411581597.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing MOFs materials have low efficiency in excitation of internal electrons under visible light conditions, which affects their photocatalytic antibacterial effects.
By constructing Z-shaped heterojunctions of ZIF-8/FeWOx nanocomposites, the efficiency of electrons and holes is reduced, making electrons easier to transition from valence band to conduction band, improve the photocatalytic performance of nanomaterials, and load them to Degradable TPU fiber membrane.
The coordinated antibacterial effect of photocatalytic, photothermal and magnetothermal has been achieved, and the killing rate of a variety of drug-resistant bacteria can reach 99.99%, providing new products for the field of medical protection.
Smart Images

Figure CN119433840A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of antibacterial nano-composite fiber materials, and in particular relates to a preparation method and application of an antibacterial nano-composite fiber membrane. Background Art
[0002] Medical staff need to wear disposable protective equipment when they come into contact with infectious disease patients to block the microparticles of the patient's blood, body fluids, and secretions. Personal protective equipment becomes a direct protective barrier for medical staff to avoid biological contamination hazards. Thermoplastic elastic polyurethane (TPU) materials have excellent biocompatibility, flexibility and elasticity, environmental protection, non-toxicity, and degradability. At the same time, polyurethane nanofibers also have excellent waterproof, moisture permeability, and breathability. They have been widely studied in the field of medical and health care.
[0003] Metal-organic framework materials (MOFs) are a type of organic-inorganic porous coordination polymers composed of metal ions or metal clusters and organic ligands. They have a topological three-dimensional network pore structure and are widely used in adsorption and separation, energy storage, sensing, antibacterial and catalysis. Zinc imidazolate framework-8 (ZIF-8) is one of the common MOFs materials and is widely used. Although ZIF-8 materials are easy to process, have high chemical stability, good biodegradability and biocompatibility, when used in the field of photocatalysis and antibacterial, due to its large bandgap and weak response to visible light, it is difficult to excite internal electrons under visible light conditions, thus affecting its solar radiation efficiency. Tungsten-doped ferrite (FeWO x ) as a magnetic nanomaterial, it has a suitable energy band structure and can form a Z-type heterojunction with ZIF-8, shortening the charge transfer distance, effectively inhibiting the recombination of electrons and holes, and improving the photocatalytic effect of nanomaterials. x It can also achieve a synergistic antibacterial effect with ZIF-8 through magnetic thermal effect.
[0004] In summary, the present invention designs and develops a photocatalytic, photothermal, and magnetic thermal synergistic antibacterial nanocomposite fiber membrane, which uses degradable, high-strength, and highly hydrophobic TPU as a substrate, and incorporates ZIF-8 / FeWO x (hereinafter referred to as ZF) nanocomposite materials, TPU-ZIF-8 / FeWO prepared by solution jet spinning technology x(hereinafter referred to as T-ZF) nanocomposite fiber membrane. The nanocomposite fiber membrane has the functions of photocatalysis, photothermal and magnetic thermal synergistic antibacterial, and the killing effect on Escherichia coli (E.coli), Staphylococcus aureus (S.aureus), multi-drug resistant Escherichia coli (MDRE.coli) and methicillin-resistant Staphylococcus aureus (MRSA) can reach 99.99%. The nanocomposite fiber membrane can provide new products for the field of medical protection. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an antibacterial nanocomposite fiber membrane and its application, and to propose ZIF-8 / FeWO for the first time. x Nanocomposite materials, by constructing a Z-type heterojunction, reduce the electron-hole recombination efficiency, make it easier for electrons to jump from the valence band to the conduction band, improve the photocatalytic performance of nanomaterials, and prepare a TPU-ZIF-8 / FeWO x A new type of nanocomposite fiber membrane. The fiber membrane uses TPU as the substrate and uses solution jet spinning technology to form a nano heterojunction ZIF-8 / FeWO x Loaded on the fiber, the fiber promotes photocatalysis through thermal effect to achieve synergistic and efficient antibacterial effect of photocatalysis, photothermal and magnetothermal. The nanocomposite fiber membrane is expected to be used in the medical and health field to provide new products for medical protection.
[0006] The technical solution adopted by the present invention is as follows:
[0007] The method for preparing the antibacterial nanocomposite fiber membrane comprises the following steps:
[0008] Step 1: Preparation of imidazole ester skeleton-8;
[0009] Step 101: adding 2.8-3.5 parts by mass of 2-methylimidazole and 1.2-1.7 parts by mass of zinc nitrate hexahydrate to 65-75 parts by mass of a methanol solution; wherein the concentration of the methanol solution is 40%-60%;
[0010] Step 102: Perform magnetic stirring at room temperature (25° C.) on a magnetic stirrer for 30 min;
[0011] Step 103: Collect the precipitate by centrifugation and wash it with methanol 5 times;
[0012] Step 104: Drying in a vacuum oven at 60° C. for 12 hours to complete the preparation of imidazole ester skeleton-8.
[0013] Step 2: preparing tungsten-doped ferrite;
[0014] Step 201: 0.8-0.85 parts by mass of 1,2-dodecanediol, 0.1-0.2 parts by mass of tungsten hexacarbonyl, 0.08-0.09 parts by mass of ferrous acetylacetonate, 0.4-0.5 parts by mass of ferric acetylacetonate, 75-85 parts by mass of diphenyl ether, 0.35-0.45 parts by mass of oleic acid, and 3.2-4 parts by mass of oleylamine are placed in a round-bottom flask;
[0015] Step 202: slowly heating to 120° C. under argon protection, maintaining for 10 min, then slowly heating to 260° C., maintaining for 2.5 h, and then immediately performing quenching treatment;
[0016] Step 203: After the reaction in step 201 is cooled to room temperature, the precipitate is collected by centrifugation and washed with ethanol and ultrapure water for 5 times;
[0017] Step 204: After vacuum freeze drying, tungsten-doped ferrite powder is obtained.
[0018] Step 3: using imidazolate skeleton-8 and tungsten-doped ferrite to complete the preparation of antibacterial nanomaterial powder;
[0019] Step 301: adding 45-50 parts by mass of imidazole ester framework-8 powder and 45-50 parts by mass of tungsten-doped ferrite powder to 25-35 parts by mass of ultrapure water,
[0020] Step 302: The solution is subjected to ultrasonic treatment for 10 minutes.
[0021] Step 303: Place the solution in a shaker for 12 hours.
[0022] Step 304: Collect the precipitate by centrifugation and wash it with ultrapure water for 5 times, and obtain the antibacterial nanomaterial powder after vacuum freeze-drying.
[0023] Step 4: Use the antibacterial nanomaterial powder and TPU particles prepared in step 3 to prepare a TPU spinning solution in which the antibacterial nanomaterial powder is evenly dispersed; and use a solution jet spinning method to obtain a composite nanofiber membrane.
[0024] Step 401: weighing 0.04-0.05 parts by mass of antibacterial nanomaterial powder and dissolving it in 1 part by mass of N,N-dimethylformamide and 2 parts by mass of tetrahydrofuran;
[0025] Step 402: Ultrasonication for 5 minutes, and then adding 0.45-0.55 parts by mass of TPU particles;
[0026] Step 403: magnetically stirring at 40° C. for 12 hours to complete the preparation of TPU spinning solution in which antibacterial nanomaterial powder is dispersed;
[0027] Step 404: The obtained spinning solution is subjected to a solution jet spinning method to obtain an antibacterial nanocomposite fiber membrane; the parameters of the jet spinning method in step 404 are: needle specification: 25G, propulsion rate: 0.25mL / h, receiving roller speed: 300rpm, receiving distance: 30cm, wind pressure: 70MPa.
[0028] Application of the antibacterial nanocomposite fiber membrane in the preparation of medical protective equipment.
[0029] The technical effects achieved by the present invention are:
[0030] The present invention discloses a photocatalytic, photothermal and magnetic thermal synergistic antibacterial nanocomposite fiber membrane, wherein the fiber uses a degradable, high-strength and high-hydrophobic TPU as a substrate, and ZIF-8 / FeWO is doped into it. x (hereinafter referred to as ZF) nanocomposite materials, TPU-ZIF-8 / FeWO prepared by solution jet spinning technology x (hereinafter referred to as T-ZF) nanocomposite fiber membrane. The nanocomposite fiber membrane has the functions of photocatalysis, photothermal and magnetic thermal synergistic antibacterial, and the killing effect on Escherichia coli (E.coli), Staphylococcus aureus (S.aureus), multi-drug resistant Escherichia coli (MDR E.coli) and methicillin-resistant Staphylococcus aureus (MRSA) can reach 99.99%. The nanocomposite fiber membrane can provide new products in the field of medical protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a schematic diagram of the preparation of the nanocomposite fiber membrane in the present invention;
[0032] Figure 2 is a SEM image of the ZIF-8 nanomaterial of the present invention;
[0033] Figure 3 is the XRD spectrum of the ZIF-8 nanomaterial in the present invention;
[0034] Figure 4 is the Zeta potential diagram of the ZIF-8 nanomaterial in the present invention (n=3);
[0035] Figure 5 The FeWO in the present invention x SEM images of nanomaterials;
[0036] Figure 6 The FeWO in the present invention x XRD patterns of nanomaterials;
[0037] Figure 7 The FeWO in the present invention x Zeta potential diagram of nanomaterials (n=3);
[0038] Figure 8 is a SEM image of the ZF nanomaterial in the present invention;
[0039] Fig. 9 is the XRD spectrum of the ZF nanomaterial in the present invention;
[0040] Fig.10 The ZIF-8 and FeWO x , FTIR spectrum of ZF;
[0041] Fig.11 The ZIF-8 and FeWO x , UV-Vis-DRS spectrum of ZF;
[0042] Fig.12 The ZIF-8 and FeWO x , ESI spectrum of ZF;
[0043] Fig.13 The ZIF-8 and FeWO x , ZF's photocurrent response spectrum;
[0044] Fig.14 The ZIF-8 and FeWO x , ZF’s 1 ESR spectrum of O2;
[0045] Fig.15 The ZIF-8 and FeWO x 、ESR spectrum of ·OH of ZF;
[0046] Fig.16 The ZIF-8 / FeWO x The energy band structure diagram of the nanocomposite material;
[0047] Fig.17The ZIF-8 and FeWO x 、ZF simulates sunlight (1000W / m 2 ) and the photothermal cycle curves of ZF under five on / off cycles;
[0048] Fig.18 The FeWO in the present invention x , hysteresis loop of ZF;
[0049] Fig.19 The ZIF-8 and FeWO x , the temperature rise curve of ZF under alternating magnetic field and the magnetothermal cycle curve of ZF under five cycles;
[0050] Fig. 20 The present invention is in different groups of ZIF-8, FeWO x and ZF's photos of different plate-spread colonies and bacterial survival quantification diagrams ( Fig. 20 Middle: 1: Control; 2: ZIF-8-Dark; 3: FeWO x -Dark; 4: ZF-Dark; 5: ZIF-8-Light; 6: FeWO x -Light; 7: ZF-Light; 8: ZIF-8-Magnetic; 9: FeWO x -Magnetic; 10: ZF-Magnetic; 11: ZIF-8-M+L; 12: FeWO x -M+L; 13: ZF-M+L) (n=3);
[0051] Fig.21 It is a physical picture of the fiber in the present invention;
[0052] Fig. 22 It is the SEM image of TPU and T-ZF fiber in the present invention;
[0053] Fig.23 is the contact angle of TPU and T-ZF fibers in the present invention (n=3);
[0054] Fig.24 The TPU, T-ZIF-8, T-FeWO x , T-ZF 1 ESR spectrum of O2;
[0055] Fig.25 The TPU, T-ZIF-8, T-FeWO x , ESR spectrum of ·OH of T-ZF;
[0056] Fig.26The TPU, T-ZIF-8, T-FeWO x 、T-ZF simulates sunlight (1000W / m 2 ) and the photothermal cycle curves of T-ZF fiber under five on / off cycles;
[0057] Fig. 27 The TPU, T-ZIF-8, T-FeWO x , the heating curve of T-ZF under alternating magnetic field and the magnetothermal cycle curve of T-ZF fiber under five thermal cooling cycles;
[0058] Fig.28 This is a diagram showing the antibacterial effect of the present invention on Escherichia coli E.coli;
[0059] Fig.29 This is a diagram showing the antibacterial effect of the present invention on Staphylococcus aureus S.aureus;
[0060] Fig.30 This is a diagram of the antibacterial effect of the present invention on multi-drug resistant Escherichia coli MDRE.coli;
[0061] Fig.31 This is a diagram showing the antibacterial effect of the present invention on methicillin-resistant Staphylococcus aureus (MRSA).
[0062] Figure 29-Figure 31 Medium: (1: Control; 2: TPU-Dark; 3: T-ZIF-8-Dark; 4: T-FeWO x -Dark; 5: T-ZF-Dark; 6: TPU-Light+Ice; 7: T-ZIF-8-Light+Ice; 8: T-FeWO x -Light+Ice; 9: T-ZF-Light+Ice; 10: TPU-Light; 11: T-ZIF-8-Light; 12: T-FeWO x -Light; 13: T-ZF-Light; 14: TPU-Magnetic; 15: T-ZIF-8-Magnetic; 16: T-FeWO x -Magnetic; 17: T-ZF-Magnetic; 18: TPU-M+L; 19: T-ZIF-8-M+L; 20: T-FeWO x -M+L; 21: T-ZF-M+L) (n=3). DETAILED DESCRIPTION
[0063] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is specifically described below in conjunction with embodiments. It should be understood that the following text is only used to describe one or several specific embodiments of the present invention, and does not strictly limit the scope of protection of the specific claims of the present invention.
[0064] Embodiment 1:
[0065] The method for preparing the antibacterial nanocomposite fiber membrane comprises the following steps:
[0066] Step 1: Preparation of imidazole ester skeleton-8;
[0067] Step 101: adding 2.8-3.5 parts by mass of 2-methylimidazole and 1.2-1.7 parts by mass of zinc nitrate hexahydrate to 65-75 parts by mass of a methanol solution; wherein the concentration of the methanol solution is 40%-60%;
[0068] Step 102: Perform magnetic stirring at room temperature (25° C.) on a magnetic stirrer for 30 min;
[0069] Step 103: Collect the precipitate by centrifugation and wash it with methanol 5 times;
[0070] Step 104: Drying in a vacuum oven at 60° C. for 12 hours to complete the preparation of imidazole ester skeleton-8.
[0071] Step 2: preparing tungsten-doped ferrite;
[0072] Step 201: 0.8-0.85 parts by mass of 1,2-dodecanediol, 0.1-0.2 parts by mass of tungsten hexacarbonyl, 0.08-0.09 parts by mass of ferrous acetylacetonate, 0.4-0.5 parts by mass of ferric acetylacetonate, 75-85 parts by mass of diphenyl ether, 0.35-0.45 parts by mass of oleic acid, and 3.2-4 parts by mass of oleylamine are placed in a round-bottom flask;
[0073] Step 202: slowly heating to 120° C. under argon protection, maintaining for 10 min, then slowly heating to 260° C., maintaining for 2.5 h, and then immediately performing quenching treatment;
[0074] Step 203: After the reaction in step 201 is cooled to room temperature, the precipitate is collected by centrifugation and washed with ethanol and ultrapure water for 5 times;
[0075] Step 204: After vacuum freeze drying, tungsten-doped ferrite powder is obtained.
[0076] Step 3: using imidazolate skeleton-8 and tungsten-doped ferrite to complete the preparation of antibacterial nanomaterial powder;
[0077] Step 301: adding 45-50 parts by mass of imidazole ester framework-8 powder and 45-50 parts by mass of tungsten-doped ferrite powder to 25-35 parts by mass of ultrapure water,
[0078] Step 302: The solution is subjected to ultrasonic treatment for 10 minutes.
[0079] Step 303: Place the solution in a shaker for 12 hours.
[0080] Step 304: Collect the precipitate by centrifugation and wash it with ultrapure water for 5 times, and obtain the antibacterial nanomaterial powder after vacuum freeze-drying.
[0081] Step 4: Use the antibacterial nanomaterial powder and TPU particles prepared in step 3 to prepare a TPU spinning solution in which the antibacterial nanomaterial powder is evenly dispersed; and use a solution jet spinning method to obtain a composite nanofiber membrane.
[0082] Step 401: weighing 0.04-0.05 parts by mass of antibacterial nanomaterial powder and dissolving it in 1 part by mass of N,N-dimethylformamide and 2 parts by mass of tetrahydrofuran;
[0083] Step 402: Ultrasonication for 5 minutes, and then adding 0.45-0.55 parts by mass of TPU particles;
[0084] Step 403: magnetically stirring at 40° C. for 12 hours to complete the preparation of TPU spinning solution in which antibacterial nanomaterial powder is dispersed;
[0085] Step 404: The obtained spinning solution is subjected to a solution jet spinning method to obtain an antibacterial nanocomposite fiber membrane; the parameters of the jet spinning method in step 404 are: needle specification: 25G, propulsion rate: 0.25mL / h, receiving roller speed: 300rpm, receiving distance: 30cm, wind pressure: 70MPa.
[0086] Embodiment 2:
[0087] Application of the antibacterial nanocomposite fiber membrane in the preparation of medical protective equipment.
[0088] Embodiment three:
[0089] The preparation method of the antibacterial nanocomposite fiber membrane comprises the following steps:
[0090] Step 1: Preparation of imidazolate framework-8 (abbreviated as ZIF-8):
[0091] 3.3 g of 2-methylimidazole and 1.5 g of zinc nitrate hexahydrate were added to 70 mL of methanol solution and stirred on a magnetic stirrer at room temperature for 30 min. The precipitate was then collected by centrifugation and washed several times with methanol, and then dried in a vacuum oven at 60 °C for 12 h.
[0092] In this embodiment, ZIF-8 was subjected to characterization experiments:
[0093] The morphology of ZIF-8 nanomaterials was obtained by scanning electron microscopy (SEM). Figure 2 As shown in FIG. 1 , the obtained ZIF-8 has a rhombic dodecahedral structure and a particle size of about 100 nm. The crystal structure was verified by X-ray powder diffractometer (XRD) analysis. The results are shown in FIG. Figure 3 As shown in Figure 2, the XRD pattern of ZIF-8 obtained corresponds to the ZIF-8 standard curve, indicating that ZIF-8 was successfully prepared. The Zeta potential of the material was measured by a Zeta potential meter. Figure 4 Shows positive charge.
[0094] Step 2: Preparation of tungsten-doped ferrite (FeWO x ):
[0095] 0.82 g 1,2-dodecanediol, 0.1126 g hexacarbonyl tungsten, 0.0812 g ferrous acetylacetonate, 0.452 g ferric acetylacetonate, 80 mL diphenyl ether, 0.4 mL oleic acid, and 3.6 mL oleylamine were placed in a round-bottom flask. The temperature was slowly raised to 120 °C under argon protection and maintained for 10 min. The temperature was then slowly raised to 260 °C and maintained for 2.5 h. The quenching treatment was then immediately performed. After the reaction was cooled to room temperature, the precipitate was collected by centrifugation and washed several times with ethanol and ultrapure water. FeWO was obtained after vacuum freeze drying. x powder.
[0096] In this embodiment, FeWO x Conduct characterization exploration experiments:
[0097] FeWO obtained by SEM x The morphology of nanomaterials. Figure 5 As shown, the obtained FeWO x It is spherical in shape, with a particle size of about 80nm. The crystal structure was verified by XRD analysis. The results are as follows Figure 6 As shown, the FeWO x XRD patterns of FeWO x The standard curve corresponds to FeWO x was successfully prepared. Figure 7 The Zeta potential of the material is shown to be negatively charged.
[0098] Step 3: Antibacterial nanomaterial powder (ZIF-8 / FeWO x ) preparation, antibacterial nanomaterial powder (ZIF-8 / FeWO x ) is referred to as ZF:
[0099] 50 mg of ZIF-8 powder was mixed with 50 mg of FeWO x The powder was added to 30 mL of ultrapure water, and the solution was first placed under ultrasonic conditions for 10 min, then placed in a shaker for 12 h, and then the precipitate was collected by centrifugation and washed several times with ultrapure water, and then vacuum freeze-dried to obtain the antibacterial nanomaterial powder (ZIF-8 / FeWO x )powder.
[0100] Antibacterial nanomaterial powder (ZIF-8 / FeWO x ) Characterization Exploration Experiment:
[0101] The morphology of ZF was obtained by SEM, such as Figure 8 As shown, ZIF-8 nanoparticles are tightly bound to FeWO x Around the particles, both rhombic dodecahedral structures and spherical structures can be observed, and the crystal size is about 200nm. The crystal structure of the sample was characterized by XRD analysis, and the diffraction peaks of ZF and its corresponding ZIF-8 and FeWO x The diffraction peaks are Fig. 9 The chemical structure and functional groups of the nanomaterials were studied by Fourier transform infrared spectroscopy (FTIR), such as Fig.10 As shown, at 421cm -1 The peak at 610 cm is attributed to the Zn-N bond. -1 The peak at 740 cm is attributed to the Fe-O bond. -1 The peak at 1421 cm is attributed to the WO bond. -1 The peak at is attributed to the CN bond. The above characterizations can further illustrate the antibacterial nanomaterial powder (ZIF-8 / FeWO x )The composite material was successfully prepared.
[0102] Experiments to explore the photocatalytic performance of ZF:
[0103] In order to evaluate the photocatalytic performance of the materials, the optical properties were first evaluated using UV-Vis diffuse reflectance spectroscopy (UV-VisDRS), such as Fig.11 As shown in Figure 2, ZF exhibits strong absorption in the visible light region. In order to evaluate the charge transfer efficiency of the material, we used an electrochemical impedance spectroscopy (EIS) test, as shown in Figure 2. Fig.12 As shown, ZIF-8 and FeWO xCompared with the Nyquist curve of ZF, it shows the smallest arc radius, which means that the migration speed of photogenerated carriers increases. In order to explore whether ZF has faster migration efficiency under the excitation of sunlight, we use transient photocurrent response to detect the material under simulated sunlight, such as Fig.13 As shown in Figure 2, the photocurrent response intensity of ZF is higher than that of ZIF-8 and FeWO. x , indicating that it will produce more current-carrying electrons under the irradiation of visible light.
[0104] In order to explore the ROS generation ability of the material, we used electron spin resonance (ESR) to detect the types of ROS generated. 2 ) After irradiation, Fig.14 As shown, three characteristic peaks were detected under the condition of adding 2,2,6,6-tetramethylpiperidine (TEMP) capture agent, and the peak intensity of the characteristic peaks was 1:1:1, proving that singlet oxygen (Singletoxygen, 1 O2) is produced, and the peak intensity of the composite material is higher than that of ZIF-8 and FeWO x , further proving the enhanced photocatalytic effect. After adding 1% hydrogen peroxide (H2O2) and 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) scavenger, Fig.15 As shown, four characteristic peaks can be detected, and the peak intensities of the characteristic peaks are 1:2:2:1, which can prove that hydroxyl radicals (·OH) are generated, and the peak value of the composite material ZF is higher than that of FeWO. x , which once again proves that the photocatalytic performance of ZF is improved.
[0105] In order to clarify the generation mechanism of the above ROS, ZIF-8 and FeWO were respectively x The band gap and valence band of ZIF-8 / FeWO were tested to calculate the conduction band and obtain x The band structure of the composite material, such as Fig.16 As shown, ZIF-8, FeWO x The two can form a Z-type heterojunction.
[0106] In this embodiment, the photothermal and magnetothermal properties of ZF are:
[0107] like Fig.17 As shown, at 1000W / m 2 Under simulated sunlight, the photothermal temperature of ZF can reach up to 55°C, proving that the material has good photothermal properties. Due to the magnetic properties of the material, the hysteresis loop is as follows Fig.18 As shown, under the action of the alternating magnetic field, Fig.19 As shown, the temperature of ZF can also reach 55°C.
[0108] In this embodiment, ZIF-8, FeWO x , Evaluation of the antibacterial properties of ZF:
[0109] In order to evaluate the antibacterial properties of the materials, we chose to explore the antibacterial effects of different nanomaterials on S. aureus and E. coli under different conditions, simulating the antibacterial effects of different nanomaterials on S. aureus and E. coli at 1000 W / m 2 The results were as follows: 1) Under the conditions of 30 minutes of simulated sunlight irradiation, 10 minutes of alternating magnetic field, and 10 minutes of alternating magnetic field followed by 1000W / m 2 The antibacterial ability of the material under the condition of 30 minutes of simulated sunlight exposure. Fig. 20 As shown, under the synergistic effect of photocatalysis and thermal effect, the antibacterial rate of ZF against the two bacteria reached 99.99%.
[0110] Step 4: TPU-ZIF-8 / FeWO x Preparation of (T-ZF) antibacterial nanocomposite fiber membrane:
[0111] 0.045 g ZF nanomaterial was weighed and dissolved in 1 mL N, N-dimethylformamide and 1 mL tetrahydrofuran, ultrasonicated for 5 min, then 0.5 g TPU particles were added, and magnetic stirring was performed at 40°C for 12 h to prepare a TPU spinning solution with uniform ZF nanomaterial dispersion. The obtained spinning solution was subjected to solution jet spinning technology to obtain a T-ZF composite nanofiber membrane.
[0112] (Specific parameters are: needle specification: 25G, propulsion rate: 0.25mL / h, receiving roller speed: 300rpm, receiving distance: 30cm, wind pressure: 70MPa)
[0113] In this example, the structural characterization of T-ZF composite nanofibers is investigated:
[0114] like Fig.21 The picture shows TPU and TPU fiber doped with 9% ZF nanomaterials. The nanofibers provide a supporting platform for ZF and evenly fix the nanomaterial ZF on its surface. Fig. 22 As shown in the figure, the SEM images show the surface morphology of TPU and T-ZF nanofibers. TPU fibers present a continuous and smooth fiber structure. On the fiber membrane containing 9% ZF, ZF nanoparticles attached to the fiber surface can be clearly seen. The hydrophobicity of the fiber can ensure a certain antibacterial effect. Fig.23 The contact angle experiment tested the hydrophobicity of the fiber. The contact angle of the TPU fiber membrane was about 110°, which has high hydrophobicity. After doping with 9% ZF, its hydrophobicity increased to about 120°.
[0115] In this example, the performance characterization of T-ZF composite nanofibers was investigated:
[0116] In this example, the photocatalytic performance of T-ZF composite nanofibers was characterized:
[0117] The present invention detects the type of ROS produced by ESR and simulates sunlight (1000W / m 2 ) After irradiation, Fig.24 As shown in Figure 2, three characteristic peaks were detected under the condition of adding TEMP capture agent, and the peak intensity of the characteristic peaks was 1:1:1, which proved that there was 1 O2 production. After adding 1% H2O2 and DMPO scavenger, Fig.25 As shown, four characteristic peaks can be detected, and the peak intensities of the characteristic peaks are 1:2:2:1, which can prove the generation of ·OH.
[0118] In this example, the photothermal and magnetothermal properties of the T-ZF nanocomposite fiber membrane were investigated:
[0119] like Fig.26 As shown, at 1000W / m 2 Under simulated sunlight, the photothermal temperature of the T-ZF nanocomposite fiber membrane can reach up to 39°C, proving that the fiber membrane still has good photothermal properties. Fig. 27 As shown, the temperature of the T-ZF nanocomposite fiber membrane can also reach 50°C.
[0120] In this embodiment, the antibacterial properties of T-ZF composite nanofibers are:
[0121] In order to evaluate the antibacterial properties of the material, we chose to explore the antibacterial effects of the material on E. coli, S. aureus, MDRE. coli, and MRSA under different conditions. The flat plate coating method intuitively shows the inactivation ability of different groups of fibers on bacteria under different stimulation conditions. 2 The results were as follows: 1) 30 minutes of sunlight exposure, 2) 10 minutes of alternating magnetic field exposure, and 3) 10 minutes of alternating magnetic field exposure followed by 1000W / m 2 The antibacterial ability of the material under the condition of 30 minutes of simulated sunlight exposure. Figure 28-Figure 31 As shown, under the synergistic effects of photocatalysis, photothermal and magnetothermal, the antibacterial rate of T-ZF nanofiber membrane against several bacteria can reach 99.99%.
[0122] The above is only a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention shall be implemented according to the conventional means in the art unless otherwise specified and limited.
Claims
1. A method for preparing an antibacterial nanocomposite fiber membrane, characterized in that: The following steps are involved: Step 1: Preparation of imidazole ester skeleton-8; Step 2: preparing tungsten-doped ferrite; Step 3: using imidazolate skeleton-8 and tungsten-doped ferrite to complete the preparation of antibacterial nanomaterial powder; Step 4: Use the antibacterial nanomaterial powder and TPU particles prepared in step 3 to prepare a TPU spinning solution in which the antibacterial nanomaterial powder is evenly dispersed; and use a solution jet spinning method to obtain a composite nanofiber membrane.
2. The method for preparing the antibacterial nanocomposite fiber membrane according to claim 1, characterized in that: In the step 1, the specific steps of preparing the imidazole ester skeleton-8 are as follows: Step 101: adding 2.8-3.5 parts by mass of 2-methylimidazole and 1.2-1.7 parts by mass of zinc nitrate hexahydrate to 65-75 parts by mass of a methanol solution; Step 102: Stirring on a magnetic stirrer for 30 minutes; Step 103: Collect the precipitate by centrifugation and wash it with methanol 5 times; Step 104: Drying in a vacuum oven to complete the preparation of imidazole ester skeleton-8.
3. The method for preparing the antibacterial nanocomposite fiber membrane according to claim 2, characterized in that: In step 101, the concentration of the methanol solution is 40%-60%; in step 102, magnetic stirring is performed at room temperature 25°C; in step 104, drying is performed in a vacuum oven at 60°C for 12 hours.
4. The method for preparing the antibacterial nanocomposite fiber membrane according to claim 1, characterized in that: In step 2, the specific steps of preparing tungsten-doped ferrite are as follows: Step 201: 0.8-0.85 parts by mass of 1,2-dodecanediol, 0.1-0.2 parts by mass of tungsten hexacarbonyl, 0.08-0.09 parts by mass of ferrous acetylacetonate, 0.4-0.5 parts by mass of ferric acetylacetonate, 75-85 parts by mass of diphenyl ether, 0.35-0.45 parts by mass of oleic acid, and 3.2-4 parts by mass of oleylamine are placed in a round-bottom flask; Step 202: slowly heating to 120° C. under argon protection, maintaining for 10 min, then slowly heating to 260° C., maintaining for 2.5 h, and immediately performing quenching treatment; Step 203: After the reaction in step 201 is cooled to room temperature, the precipitate is collected by centrifugation and washed with ethanol and ultrapure water for 5 times; Step 204: After vacuum freeze drying, tungsten-doped ferrite powder is obtained.
5. The method for preparing the antibacterial nanocomposite fiber membrane according to claim 1, characterized in that: The step 3 comprises the following specific steps: Step 301: adding 45-50 parts by mass of imidazole ester framework-8 powder and 45-50 parts by mass of tungsten-doped ferrite powder to 25-35 parts by mass of ultrapure water; Step 302: treating the solution under ultrasonic conditions for 10 minutes; Step 303: placing the solution in a shaker for 12 hours; Step 304: Collect the precipitate by centrifugation and wash it with ultrapure water for 5 times, and obtain the antibacterial nanomaterial powder after vacuum freeze-drying.
6. The method for preparing the antibacterial nanocomposite fiber membrane according to claim 1, characterized in that: The step 4 comprises the following specific steps: Step 401: weighing 0.04-0.05 parts by mass of antibacterial nanomaterial powder and dissolving it in 1 part by mass of N,N-dimethylformamide and 2 parts by mass of tetrahydrofuran; Step 402: Ultrasonication for 5 minutes, and then adding 0.45-0.55 parts by mass of TPU particles; Step 403: magnetically stirring at 40° C. for 12 hours to complete the preparation of TPU spinning solution in which antibacterial nanomaterial powder is dispersed; Step 404: The obtained spinning solution is subjected to a solution jet spinning method to obtain an antibacterial nanocomposite fiber membrane.
7. The method for preparing the antibacterial nanocomposite fiber membrane according to claim 6, characterized in that: The parameters of the jet spinning method in step 404 are: needle specification: 25G, propulsion rate: 0.25mL / h, receiving roller speed: 300rpm, receiving distance: 30cm, wind pressure: 70MPa.
8. Use of the antibacterial nanocomposite fiber membrane according to any one of claims 1 to 7 in the preparation of medical protective equipment.
Citation Information
Patent Citations
Flexible MOFs / oxide semiconductor nanofiber membrane and preparation method thereof
CN114395862A
Iron-nitrogen double-doped carbon nano composite material and preparation method thereof
CN114824327A
Drug-loaded metal organic framework composite electrostatic spinning fiber membrane as well as preparation method and application thereof
CN114855365A
ZIF-8 (at) gentamicin doped nanofiber membrane as well as preparation method and application of ZIF-8 (at) gentamicin doped nanofiber membrane
CN116173280A
Free-standing MOF-derived hybrid porous carbon nanofiber mats
US20190020028A1